1994
DOI: 10.1007/bf00301684
|View full text |Cite
|
Sign up to set email alerts
|

Bone mass in female cynomolgus macaques: A cross-sectional and longitudinal study by age

Abstract: A cross-sectional study by age was designed to evaluate and describe the bone mineral content (BMC, g) and density (BMD, g/cm2) in a population of female cynomolgus macaques (Macaca fascicularis). Dual-energy X-ray absorptiometry was used to measure, in segments L2-L4 of the lumbar spine, the BMC (BMCs), BMD (BMDs), length, and total-body BMC(BMCTB) in 171 female monkeys ranging in age between 3.7 and 22.0 years. The animals were divided into three age groups: (1) young (< 6.5 years, n = 51); (2) adult (> 6.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
3
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 20 publications
4
59
3
1
Order By: Relevance
“…Jayo et al [18] recently suggested that female cynomolgus monkeys achieve peak bone-mass at the age of 9, a result confirmed by our study, but Jayo et al found that the bone mass tended to decrease in older mature animals (>13.5 years), whereas we found no such decrease. The lumbar spine of cynomolgus monkeys consists of 7 vertebrae.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Jayo et al [18] recently suggested that female cynomolgus monkeys achieve peak bone-mass at the age of 9, a result confirmed by our study, but Jayo et al found that the bone mass tended to decrease in older mature animals (>13.5 years), whereas we found no such decrease. The lumbar spine of cynomolgus monkeys consists of 7 vertebrae.…”
Section: Discussionsupporting
confidence: 88%
“…Only a few studies have shown that macaques undergo a natural pattern of change in bone mineralization that parallels the changes seen in humans. Previous studies suggest that bone mass peaks at 10-14 years of age in rhesus monkeys [3,28] and around 9 years of age in cynomolgus monkeys [18]. Precise determination of this peak will be important in the study of diseases associated with bone remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…OVX cynomolgus monkeys had increased serum levels of alkaline phosphatase and acid phosphatase compared with intact and hormone-supplemented animals (Jerome et al, 1994).…”
Section: Primates (Non-human)mentioning
confidence: 86%
“…Unfortunately, peak bone mass is not reached in cynomolgus monkeys until 9 years of age (Jayo et al, 1994), and most studies have used OVX monkeys aged 4-7 years (Jerome et al, 1993). Intuitively, OVX in the skeletally immature primate is an inappropriate model for postmenopausal osteoporosis.…”
Section: Primates (Non-human)mentioning
confidence: 99%
“…Καθώς η μετεμμηνοπαυσιακή οστεοπόρωση είναι ένα ορμο νικά εξαρτώμενο νόσημα στον άνθρωπο, οι ομοιότη τες που παρατηρούνται μεταξύ του ανθρώπου και των πρωτευόντων στα ενδοκρινικά τους συστήματα είναι ένα σημαντικό πλεονέκτημα ως προς τη χρήση των πρωτευόντων στην έρευνα της μετεμμηνοπαυσιακής οστεοπόρωσης. Δυστυχώς, η ηλικία απόκτησης κορυ φαίας οστικής πυκνότητας σε αυτά τα ζωικά είδη (cynomolgus maqaques) επέρχεται μετά την ηλικία των 9 ετών (Jayo et al 1994), ενώ οι περισσότερες μελέτες οστεοπόρωσης έχουν πραγματοποιηθεί σε ωοθηκε-κτομημένα πρωτεύοντα ηλικίας μόλις 4-7 ετών (Jerome et al 1993). Η απώλεια των οιστρογόνων σε σκελετικά ανώριμα ζωικά πρότυπα δεν είναι κατάλ ληλο πρότυπο για τη μελέτη της μετεμμηνοπαυσιακής οστεοπόρωσης.…”
Section: πρωτεύονταunclassified